2008
DOI: 10.1002/app.28898
|View full text |Cite
|
Sign up to set email alerts
|

Cure behavior and thermal stability analysis of multiwalled carbon nanotube/epoxy resin nanocomposites

Abstract: As-received multiwalled carbon nanotubes (MWCNTs) were first treated by a 3 : 1 (v/v) mixture of concentrated H 2 SO 4 /HNO 3 and further functionalized by ethylenediamine/dicyclohexylcarbodiimide/tetrahydrofuran solution. MWCNT/epoxy nanocomposites were prepared. Their cure behaviors were investigated by dynamic differential scanning calorimetry. Quantitative analysis of the activation energy as a function of the degree of curing was carried out by the Flynn-Wall-Ozawa method. The fitted multiple regression e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 21 publications
0
47
0
Order By: Relevance
“…This behavior was also observed in Figure 1b, indicating that a high degree of cure was achieved with the applied cure conditions. Although some reports have shown that CNT may change the cure reaction parameters of epoxy resins [23][24][25] , the FTIR spectra also show that the incorporation of 0.25 wt% MWCNT did not affect the final cure process of the neat or hybrid epoxy matrix. No spectroscopic change was observed with the incorporation of the MWCNT due, probably, to the low concentration of MWCNT presented in the nanocomposite and also because no reaction between MWCNT and epoxy/silsesquioxanes was expected.…”
Section: Epoxy/silsesquioxanes Hybrid Nanocomposites: Spectroscopic Amentioning
confidence: 72%
“…This behavior was also observed in Figure 1b, indicating that a high degree of cure was achieved with the applied cure conditions. Although some reports have shown that CNT may change the cure reaction parameters of epoxy resins [23][24][25] , the FTIR spectra also show that the incorporation of 0.25 wt% MWCNT did not affect the final cure process of the neat or hybrid epoxy matrix. No spectroscopic change was observed with the incorporation of the MWCNT due, probably, to the low concentration of MWCNT presented in the nanocomposite and also because no reaction between MWCNT and epoxy/silsesquioxanes was expected.…”
Section: Epoxy/silsesquioxanes Hybrid Nanocomposites: Spectroscopic Amentioning
confidence: 72%
“…This indicates that the hybrid coating does not develop good contact with the smooth copper surface and thus, despite its ~2× higher thermal conductivity vs. the 6 wt.% CBP/rubbery epoxy composite, the hybrid coating was unable to perform much better. It can also be observed 20 from Fig. 7 GNPs are less oriented parallel to interface (i.e., more GNPs are standing perpendicular to the interfacial surfaces) than on the smooth surface and this might result in the higher thermal conductivity of hybrid coating between rough surface.…”
Section: Thermal Contact Resistance Of Cb/gnp/rubbery Epoxy Hybrid Comentioning
confidence: 93%
“…Consequently, H can be regarded as a constant over the whole curing reaction. From a dynamic DSC run, the total area of the exothermal peak (the region between the exotherm and the baseline) is in direct proportion to the molar reaction heat, the H released during the whole cure reaction [34,35]. The extent of the curing at any temperature can be expressed as…”
Section: Curing Kineticsmentioning
confidence: 99%
“…It is known that curing can be monitored by the FTIR technique [34,36]. In this study, the degree of curing of the f-CNT/epoxy nanocomposite was calculated.…”
Section: Degree Of Curing By Ftirmentioning
confidence: 99%